PENGARUH KETERBATASAN UANG SAKU DAN PENGGUNAAN PAYLATER TERHADAP PENGELOLAAN KEUANGAN MAHASISWA DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MODERASI - Aulia, Mutiara; Hendratni, Tyahya Whisnu Hendratni; Nisa, Chaerani; Kaniati, Rika (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
The rapid development of digital financial services has significantly influenced students’ financial behavior, particularly in managing personal finances amid limited allowances and the increasing use of paylater services. This study aims to analyze the effect of allowance constraints and paylater usage on students’ financial management, with financial literacy as a moderating variable. The population of this study consists of university students domiciled in the Greater Jakarta area (JABODETABEK). The sampling technique employed was non-probability sampling using the purposive sampling method. Data were collected through an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that allowance constraints have a positive and significant effect on students’ financial management, while paylater usage does not have a significant effect. Furthermore, financial literacy has a positive and significant effect on students’ financial management. However, financial literacy does not moderate the relationship between allowance constraints and students’ financial management, nor does it moderate the relationship between paylater usage and students’ financial management. The R-square value of 0.896 indicates that the proposed model has strong explanatory power. These findings suggest that students’ financial management is more strongly influenced by allowance constraints and financial literacy than by the use of paylater services